The Ecological Crisis and the Spirit of Progress. An Examination at the Limits of the Modern Narrative of Growth - Lühmann, Michael (Momentum Quarterly, 2014)
Belief and hope in progress are closely intertwined with the idea and the epoch of modernity. Even though today’s concept of progress did not rely on a simplistic teleology, the narrative of economic growth as well as the supposed counter-narrative of ecological modernization in consequence still believe in the mythical promise of progress. Taking the necessity of regress as an indispensable counterpart and complement of progress as a starting point, the paper asks for the ecological limits of growth, which can delimitate or even close the supposed bound- less “horizon of expectations” of the modern era. The answer to the ecological and social crisis has to be sought in the suspension of a political agenda that is strongly influenced by the modernization theory, also culminating in the Green New Deal. In consequence the paper tries to get to the bottom of the modern concept of progress by asserting a Sattelzeit of another, an ecologic, modern age.
Keywords: progress; modern age; ecological crisis; Green New Deal; post-growth; sustainability; history of concepts